2020
DOI: 10.1088/2040-8986/abcc56
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the brightness of harmonic XUV radiation with spatially-tailored driver beams

Abstract: Bright high harmonic sources can be produced by loosely focussing high peak power laser pulses to exploit the quadratic scaling of flux with driver spot size at the expense of a larger experimental footprint. Here, we present a method for increasing the brightness of a harmonic source (while maintaining a compact experimental geometry) by spatially shaping the transverse focal intensity distribution of a driving laser from a Gaussian to supergaussian. Using a phase-only spatial light modulator we increase the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 20 publications
(27 reference statements)
0
8
0
Order By: Relevance
“…Treacher et al (2020) demonstrated that an SLM can be used to create super-Gaussian spatial profiles to drive and improve the brightness of single harmonics [50]. The technique used imprinted a π-phase shift transversely onto a collimated Gaussian beam.…”
Section: π-Shift Shaping Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Treacher et al (2020) demonstrated that an SLM can be used to create super-Gaussian spatial profiles to drive and improve the brightness of single harmonics [50]. The technique used imprinted a π-phase shift transversely onto a collimated Gaussian beam.…”
Section: π-Shift Shaping Methodsmentioning
confidence: 99%
“…where a single phase step caused the centre and periphery of the beam to interfere at the focus, changing the transverse intensity profile. Further details on the π-shift shaping method for HHG can be found in references [48,50].…”
Section: π-Shift Shaping Methodsmentioning
confidence: 99%
See 3 more Smart Citations